2023
DOI: 10.3389/fgene.2023.1168713
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-induced DNA damage, genetic, and epigenetic alterations

Abstract: Thallium (Tl) is a toxic heavy metal responsible for noxious effects in living organisms. As a pollutant, Tl can be found in the environment at high concentrations, especially in industrial areas. Systemic toxicity induced by this toxic metal can affect cell metabolism, including redox alterations, mitochondrial dysfunction, and activation of apoptotic signaling pathways. Recent focus on Tl toxicity has been devoted to the characterization of its effects at the nuclear level, with emphasis on DNA, which, in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Tl + is known to be molecularly more stable than Tl 3+ , which has strong oxidizing capacity ( Harris and Messori, 2002 ). Sánchez-Chapul et al (2023) demonstrated that the DNA double helix and its oxidization were not altered by Tl + . In contrast, Nowicka et al (2013) showed that Tl + is oxidized to Tl 3+ by experimental UV irradiation and the presence of oxygen and that Tl 3+ oxidizes guanine residues in DNA to 8-oxoguanine, inducing DNA breaks and exerting mutagenic effects.…”
Section: Toxicological Mechanismmentioning
confidence: 96%
See 1 more Smart Citation
“…Tl + is known to be molecularly more stable than Tl 3+ , which has strong oxidizing capacity ( Harris and Messori, 2002 ). Sánchez-Chapul et al (2023) demonstrated that the DNA double helix and its oxidization were not altered by Tl + . In contrast, Nowicka et al (2013) showed that Tl + is oxidized to Tl 3+ by experimental UV irradiation and the presence of oxygen and that Tl 3+ oxidizes guanine residues in DNA to 8-oxoguanine, inducing DNA breaks and exerting mutagenic effects.…”
Section: Toxicological Mechanismmentioning
confidence: 96%
“…They were banned in 1965 in the United States due to concerns about environmental pollution and high toxicity ( Riyaz et al, 2013 ). However, they are still used in many developing countries ( Sánchez-Chapul et al, 2023 ). 201 Tl-thallous chloride has been used in myocardial imaging to evaluate ischemic heart disease; this radioactive Tl emits X-rays and gamma-rays and is intravenously administered ( Genchi et al, 2021 ).…”
Section: Production and Use Of Tlmentioning
confidence: 99%